soln1

# soln1 - EE 562a Homework Solutions 1 21 Jan 2007 1 1...

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: EE 562a Homework Solutions 1 21 Jan 2007 1 1. Concave (convex ∩ ) functions have the property that every chord of the function lies below the function, as indicated in the defining equation. g ( αx + (1- α ) y ) ≥ αg ( x ) + (1- α ) g ( y ) for all x,y ∈ R It should be clear that a concave function g ( x ) has a first derivative g ( x ) that is a monotone- decreasing function of x , and hence the second derivative g 00 ( x ) is non-positive. This means that tangent lines to the function g ( x ) at any point x o lie on or above the function g ( x ). Hence g ( x ) ≤ g ( x o ) + g ( x o )( x- x o ) . We can put in x ( u ) for the variable x above and ensemble averaging both sides maintains the sense of the inequality. Then ensemble-averaging gives E { g ( x ( u )) } ≤ g ( x o ) + g ( x o )( E { x ( u ) } - x o ) . The result will of course be a function of the choice of x o . This can be simplified somewhat by choosing x o = E { x ( u ) } , yielding the result E { g ( x ( u )) } ≤ g ( E { x ( u ) } ) . 2. Since the process y ( u,t ) is defined recursively by y ( u, 1) = (1- p ) 1 / 2 x ( u, 1) , and y ( u,t ) = p 1 / 2 y ( u,t- 1) + (1- p ) 1 / 2 x ( u,t ) , t ≥ 2 , the first step is to get an explicit expression for the y ’s in terms of the x ’s: y ( u,t ) = (1- p ) 1 / 2 t X j =1 p ( t- j ) / 2 x ( u,j ) . Recall that E { x ( u,t ) } = 0 and E { x ( u,t 1 ) x ( u,t 2 ) } = δ t 1 t 2 . Then m y ( t ) = E { y ( u,t ) } = E (1- p ) 1 / 2 t X j =1 p ( t- j ) / 2 x ( u,j ) = (1- p ) 1 / 2 t X j =1 p ( t- j ) / 2 E { x ( u,j ) } = 0 , so all the random variables y ( u,t ) have zero mean. Without loss of generality, let’s assume that t 1 ≥ t 2 . The correlation functions are then R y ( t 1 ,t 2 ) = E { y ( u,t 1 ) y ( u,t 2 ) } = E (1- p ) 1 / 2 t 1 X j =1 p ( t 1- j ) / 2 x ( u,j ) (1- p ) 1 / 2 t 2 X k =1 p ( t 2- k ) / 2 x ( u,k ) ! = (1- p ) t 1 X j =1 t 2 X k =1 p ( t 1 + t 2- j- k ) / 2 E { x ( u,j ) x ( u,k ) } 2 EE 562a Homework Solutions 1 21 Jan 2007 = (1- p ) t 1 X j =1 t 2 X k =1 p ( t 1 + t 2- j- k ) / 2 δ jk = (1- p ) t 2 X j =1 p ( t 1 + t 2 ) / 2- j = (1- p ) p ( t 1- t 2 ) / 2 t 2 X j =1 p t 2- j = (1- p ) p ( t 1- t 2 ) / 2 t 2- 1 X k =0 p k . We can now use the identity t- 1 X k =0 p k = 1- p t 1- p , to get the final expression R y ( t 1 ,t 2 ) = (1- p ) p ( t 1- t 2 ) / 2 1- p t 2 1- p = p ( t 1- t 2 ) / 2- p ( t 1 + t 2 ) / 2 . 3. (a) The AM signal is given by z ( u,t ) = x ( u,t ) cos(2 πf t + θ ( u )) , where x ( u,t ) k θ ( u ) , ∀ t , and θ ( u ) is uniformly distributed on (0 , 2 π ]. First, we find the mean = ⇒ m z ( t ) = E { z ( u,t ) } = E { x ( u,t ) cos(2 πf t + θ ( u )) } = E { x ( u,t ) } E { cos(2 πf t + θ ( u )) } , where we used the fact that, since θ ( u ) k x ( u,t ) for all t , we have that x ( u,t ) and w ( u,t ) = cos(2 πf t + θ ( u )) are uncorrelated real random processes (i.e. R xw ( t 1 ,t 2 ) = m x ( t...
View Full Document

{[ snackBarMessage ]}

### Page1 / 10

soln1 - EE 562a Homework Solutions 1 21 Jan 2007 1 1...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online